(untitled) (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2010)
Comparative analysis of literature data of synthesis of oxide superconducting materials, particularly Bi-containing cuprates, have been made. It was shown that depending of HTSC product and field of its using different ways of synthesis can be appropriate.